LEGAL ANALYSIS ON THE INFLUENCE VICTIMS' ROLE IN CRIMINAL ACTS OF SEXUAL VIOLENCE - Wiryawan Batara Kencana; Syamsuddin Muchtar; Wiwie Heryani (fakultas hukum universitas PGRI Semarang, 2023)
Victims, who also acts as a participant in the occurrence of a crime, essentially have a functional role. This role arises from certain conditions and situations that are basically attached to the victim, so it is necessary to know the type or category of the victim that can influence the occurrence of a crime of sexual violence. The type of research used in this research is normative legal research. The research approach used is a statute approach and a case approach.The result shows that the categorization of victims that can influence the sexual violence crime (TPKS) is victims with passive causes, victims with active causes, and victims who are also perpetrators